Clinical Practice Curriculum in the Field of Teacher Education in China: Connotation, Characteristics, and Construction Direction - Yu, Houmo (Journal of Education, Health and Sport, 2025)
The clinical practice curriculum in teacher education cultivates "clinical expert teachers" through authentic educational environments. By diagnosing, intervening in, and reflecting on teaching challenges, it integrates theory with practice, addressing issues like "knowledge representation gaps" and "stereotyped teaching behaviors." However, influenced by traditional objectivist epistemology, clinical practice in China remains marginalized, with education-related courses comprising only about 10% of total instructional hours—insufficient for developing practical knowledge and clinical competence. While prior research has explored theoretical foundations, characteristics, and models, studies remain fragmented, lacking a coherent framework where "theory informs characteristics, characteristics guide pathways, and pathways refine theory." This study proposes a tripartite "connotation–characteristics–pathways" framework, articulating principles of contextual embeddedness, problem-oriented teaching, and reflective practice; identifying field-based, problem-focused, and critical dimensions; and advancing a "four-in-one" plan targeting cognitive-competency-affective development, integrated structures, collaborative implementation, and multi-evidence evaluation.